Andrographolide and its Derivatives in Cardiovascular Disease: A Comprehensive Review - Zhang, Shenjie; Xie, Xiaokai; Zhao, Juan; Jiang, Yilong; Huang, Chao; Li, Qi; Xia, Boyu; Yin, Le; Yuan, Xiaomei; You, Qingsheng (Planta Medica, 2025)
Cardiovascular disease is one of the main causes of mortality worldwide. Andrographolide represents an important category of natural phytochemicals that has significant therapeutic potential in various conditions such as acute lung injury, heart disease, and viral infections due to its anti-oxidative, anti-inflammatory, and anti-apoptotic properties. This compound plays a protective role in human pathophysiology. This review provides a comprehensive overview of the effects of andrographolide on cardiovascular disease and examines its essential roles and mechanisms in cardiovascular disease and other vascular dysfunctions. The data collected in this review serve as a comprehensive reference for the role of andrographolide in cardiovascular disease and provide valuable insights for further research and the development of andrographolide as a novel therapeutic approach for cardiovascular disease.
Keywords: andrographolide; cardiovascular disease; heart